Enhanced nZEB concept incorporating a sustainable Grid Support Scheme. (May 2021) - Kotarela, F.; Kyritsis, A.; Papanikolaou, N.; Kalogirou, S.A.
Abstract: The building sector in Europe represents a large amount of the total energy consumption. European Union policies urge energy management systems installation in buildings, to achieve the nZEB targets and mitigate the climate change. Except for renewable energy sources, the incorporation of energy storage units (ESUs) is of major importance for building energy management, in order to increase self-consumption levels. The present work contributes to the mass installation of ESUs in building sector, as a tool to provide flexibility in the distributed production of energy. This concept is an enhanced version of nZEBs that is able to compete in the Electricity Market, and to contribute to the reliability and flexibility of the electricity grid as an alternative to centralized ESUs investments. In this context, the present work proposes a new type of grid ancillary services for building sector and a novel Grid Support Scheme (GSS) that considers both the energy fluctuations of the available energy in the ESU as well as the energy transactions with the grid. The proposed GSS model concludes to a pricing policy relying on the Value of Lost Load (VoLL), in order that the proposed grid support investment becomes sustainable. The validation of the GSS is performed by means of Life Cycle Cost Assessment. Highlights: A Grid Support Business Scheme (GSS) suitable for nZEBs is presented. nZEBs energy storage units (ESUs) are utilized to provide flexibility in electricity grid. LCCA is used to examine the sustainability of the proposed GSBM model. Contribution to the mass installation of ESUs in building sector. The present work proposes a way that nZEBs can participate in Electricity Market.